Le Touat dans la globalité médiévale - Hadrien Collet; Ingrid Houssaye Michienzi (Revue des Mondes Musulmans et de la Méditerranée)
The Datini collection in the archives of Prato in Tuscany, through its correspondence and account books, sheds light on the circulation of shipments of copper mined in the kingdom of Hungary, transported to Venice, and shipped to northern Africa via Mallorca, then to sub-Saharan Africa via the Touat, around 1400. The rich content of the correspondence exchanged between various subsidiaries of the Datini company fills an important gap in the documentation on African connections and routes. The purpose of this article is thus to unveil the stakes and modalities of such a trade, by highlighting the routes and the actors. The first part is a precise and detailed presentation of the copper shipments including important data. Reference is made to the quality of the copper and its shapes (rods, ingots, plates, etc.), trade routes, intermediaries, etc. This first part describes the route of copper from the Hungarian kingdom to the Touat, a Saharan crossroads then in full expansion. The second part follows on and offers a synthesis of the state of knowledge on the question of copper in the context of the great trans-Saharan trade and its southern West African outlets (Sahel, forest zone). The main purpose is to show how the data in the Datini collection can shed new light on the geopolitics of copper in the Sahara and the Sahel around 1400 and contribute to enrich a patchy documentation and provide material for the development of new theories and ideas.